2011
DOI: 10.1080/14786419.2010.547859
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of a genipin blue from egg protein and genipin

Abstract: Genipin blue is a pigment prepared from the reaction of genipin with amino acid. We describe herein a new method used to prepare genipin blue, water-soluble blue pigments, through the reaction of hen egg protein with genipin. The effects of reaction time, reaction temperature, the pH value of the solution and the mass ratio of the reactants on the preparation are studied. One part of genipin reacted with eight parts of hen egg protein (w/w) in water (pH value of reaction system 7.5) at 60°C for 96 h and gave b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…A previous study [20] suggested that some peptide-containing substances, such as egg white, can replace amino acids as substrate, which would facilitate mass production of gardenia blue [ 21 ]. Moreover, gardenia blue can be used as a sensitizer in dye-sensitized solar cells [22] , [23] used for photosensitized power generation.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study [20] suggested that some peptide-containing substances, such as egg white, can replace amino acids as substrate, which would facilitate mass production of gardenia blue [ 21 ]. Moreover, gardenia blue can be used as a sensitizer in dye-sensitized solar cells [22] , [23] used for photosensitized power generation.…”
Section: Discussionmentioning
confidence: 99%
“…This reaction will cause dimerization. The mixtures of polymers formed from these reactions are the reason of blue pigment 20) . In our study, light blue SF-G scaffolds were obtained in cross-linked group in different pre-freezing temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular structure of the polymers and pigment composition depend on the amino source, genipin to amino acid ratio, and pH during reaction (Fujikawa et al, 1987;Konga et al, 1989;Lee et al, 2003;Vargas Cano et al, 2014;Yang et al, 2012). Due to the strong impact of reaction conditions on the polymeric products, their structural elucidation has been poorly investigated so far.…”
Section: Structurementioning
confidence: 99%